2020
DOI: 10.3390/jcm9113774
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Use of Mechanical Restraints in Psychiatry: A New Challenge in the Everyday Clinical Practice at the Time of COVID-19

Abstract: Restraining interventions, which comprise physical (PR) and mechanical restraint (MR), have a long history in mental health services [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Numerous studies have demonstrated the benefits of managing violent situations or agitated patients by means of verbal de-escalation techniques (Berring et al 2016;Cusack et al 2016;Fern andez-Costa et al 2020;Garriga et al 2016;Hallett & Dickens 2015, 2017Jury et al 2019;Kuivalainen et al 2017;Lavelle et al 2016;Mavandadi et al 2016;McKeown et al 2019;Price et al 2015Price et al , 2018Richmond et al 2012). In addition to the reduced intervention time, other authors have described the following benefits: (i) avoiding violence and preventing harm without having to resort to mechanical restraint or isolation (Fern andez-Costa et al 2020;Jury et al 2019), (ii) verbal de-escalation helps nurses develop better relationships with their patients (Garriga et al 2016), increasing self-esteem, and job satisfaction (Cowin et al 2004;De Berardis et al 2020;Price et al 2018), (iii) verbal de-escalation is less time-consuming than the process of mechanical restraint and involuntary medication (Richmond et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the benefits of managing violent situations or agitated patients by means of verbal de-escalation techniques (Berring et al 2016;Cusack et al 2016;Fern andez-Costa et al 2020;Garriga et al 2016;Hallett & Dickens 2015, 2017Jury et al 2019;Kuivalainen et al 2017;Lavelle et al 2016;Mavandadi et al 2016;McKeown et al 2019;Price et al 2015Price et al , 2018Richmond et al 2012). In addition to the reduced intervention time, other authors have described the following benefits: (i) avoiding violence and preventing harm without having to resort to mechanical restraint or isolation (Fern andez-Costa et al 2020;Jury et al 2019), (ii) verbal de-escalation helps nurses develop better relationships with their patients (Garriga et al 2016), increasing self-esteem, and job satisfaction (Cowin et al 2004;De Berardis et al 2020;Price et al 2018), (iii) verbal de-escalation is less time-consuming than the process of mechanical restraint and involuntary medication (Richmond et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2004; De Berardis et al . 2020; Price et al . 2018), (iii) verbal de‐escalation is less time‐consuming than the process of mechanical restraint and involuntary medication (Richmond et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, de-escalation techniques to manage aggressive behaviors have been provided: always respect the personal space of the patient while maintaining a protected position with the possibility to escape, do not be provoking or offensive, create verbal contact and do not often make eye contact, be concise and communicate clearly, recognize patients' needs and feelings, pay attention to what the patient is saying without lying to them, agree or agree to disagree with the patient's thoughts and sensations, lay down the law and set clear and definite confines, propose sincerely the patient's choices and try to gain their trust, debrief the subject and the staff after the de-escalation [12]. Furthermore, in terms of diagnosis and severe psychopathological conditions, aggressive behaviors are often detectable and MR could be limited and prevented with the use of adequate pharmacological treatment, especially because the first three days are related to the highest prevalence rates of aggressive behaviors [45].…”
Section: Discussionmentioning
confidence: 99%
“…This traumatic event is a very rare phenomenon; however, permanent lesions (of the wrist, legs, nerves), respiratory distress, venous thromboembolism, deep vein thrombosis, especially if the MR is prolonged, could frequently occur. Furthermore, patients report decreased self-esteem and empowerment, strong feelings of humiliation, as well as loss of trust in healthcare personnel [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is currently unknown whether R/S intervention use changed in other clinical settings, such as EDs, which saw dramatic changes in service provision during the pandemic [4,[10][11][12]. Similarly, existing research has focused solely on R/S use for patients with MH issues [33][34][35][36][37][38][39][40][41], despite the fact that SU-related concerns increased on par with MH-related concerns during the pandemic [19][20][21][22][23][24][25][26] and are a known risk factor for the use of R/S interventions [42,43].…”
Section: Current Studymentioning
confidence: 99%